LOCAL AREA STRATEGY AND ASSESSMENT OF LOCAL GOVERNING PRACTICE SUCCESS - S. L. Baydakov (Модернизация, инновация, развитие, 2015)
The article demonstrates strategic vector of local area development as methodological basement for strategy design as well as sustainable development and quality of life concepts as the instruments for governing success criteria selection.